Diagnostic Approach to Anorectal Malformations in Neonates - Syifa Ainayah Alfaatihah; Aziz Beru Gani; Rizka Anastasia (Journal La Medihealtico, 2026)
an incidence of approximately 1 in 5,000 live births. The wide spectrum of abnormalities necessitates accurate classification and early diagnosis during the neonatal period to guide appropriate surgical management and predict long-term continence outcomes. One of the major diagnostic challenges lies in the limitations of conventional invasive techniques and the potential risks associated with radiation exposure. This study aims to identify effective diagnostic approaches for ARM in neonates. This research employs a literature review design with a narrative review approach. The data consist of secondary sources derived from 20 selected studies, including national and international journals as well as textbooks published between 2014 and 2025, accessed through databases such as ClinicalKey and Google Scholar. The analysis focuses on clinical, radiological, prenatal, and systemic factors relevant to establishing an accurate diagnosis. The findings indicate that diagnosis should begin with a thorough perineal physical examination to identify fistulas and signs of obstruction. A high-pressure distal colostogram remains the gold standard for delineating fistula anatomy prior to surgery. In addition, high-resolution transperineal ultrasound and magnetic resonance imaging have emerged as reliable non-invasive modalities for evaluating rectal position and the sphincter muscle complex. Anorectal manometry also plays a significant role in detecting subtle forms of ARM that may be overlooked during routine examinations. A systematic and multidisciplinary diagnostic approach that integrates clinical assessment, screening for associated anomalies, and multimodal imaging is essential to optimize surgical planning and improve patient outcomes.